2014
DOI: 10.1039/c3gc42589d
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient, NiAu-catalyzed hydrogenolysis of lignin into phenolic chemicals

Abstract: A highly efficient, stable NiAu catalyst that exhibits unprecedented low temperature activity in lignin hydrogenolysis was for the first time developed, leading to the formation of 14 wt% aromatic monomers from organosolv lignin at 170 °C in pure water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
140
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 247 publications
(144 citation statements)
references
References 48 publications
(70 reference statements)
2
140
2
Order By: Relevance
“…It was proposed that the improved yield from combining Raney Ni with a zeolite arose from the latter hindering the reaction between the parent lignin and other more reactive lignin fragments that could together to produce high molecular weight oligomers. Bimetallic NiM (M = Ru, Rh, Pd, Au, Mo) catalysts have also been studied for lignin hydrogenolysis [33,34], [35] [36], wherein NaOH addition proved beneficial, promoting the formation of aromatic compounds and supressing arene hydrogenation. Konnerth et al [37] also observed increased Organosolv lignin depolymerization via NaOH addition to the aqueous reaction mixture containing an Ni 7 Au 3 Fig.…”
Section: Hydrogenolysismentioning
confidence: 99%
“…It was proposed that the improved yield from combining Raney Ni with a zeolite arose from the latter hindering the reaction between the parent lignin and other more reactive lignin fragments that could together to produce high molecular weight oligomers. Bimetallic NiM (M = Ru, Rh, Pd, Au, Mo) catalysts have also been studied for lignin hydrogenolysis [33,34], [35] [36], wherein NaOH addition proved beneficial, promoting the formation of aromatic compounds and supressing arene hydrogenation. Konnerth et al [37] also observed increased Organosolv lignin depolymerization via NaOH addition to the aqueous reaction mixture containing an Ni 7 Au 3 Fig.…”
Section: Hydrogenolysismentioning
confidence: 99%
“…Monometallic Ni catalyst showed a conversion of 35.8% with 25.5% monomer yield, whereas monometallic Ag catalyst was almost inert for this reaction. [55] Interestingly, NiAg prepared from different precursors exhibited distinctively different activities. Over Ni 0.5 Ag 0.5 -A, which was derived from acetate precursors, similar monomer and dimer yields were achieved as compared to monometallic Ni catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…[56] Notably, gold, which itself was almost inert in the hydrogenolysis of β-O-4 linkage, unpredictably exhibited similar promotional effect compared with Ru, Pt, and Pd. [55] Silver is in the same group with gold, and is cheaper and more abundant. This prompted us to develop a bimetallic NiAg catalyst for lignin hydrogenolysis.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hydrogenolysis, catalytic cracking, and solvothermal treatment were the main methods adopted [4,5], and a satisfied yield of monophenols was obtained [6,7]. A high yield of monophenols was achieved by Zhao et al via the catalytic hydrogenation process [8].…”
Section: Introductionmentioning
confidence: 99%